Biomechanical and anthropometric factors that differentiate national- and regional-level judo players - Teixeira, F. G.; Rosa, P. T. C. R.; Mello, R. G. T.; Nadal, J. (International Journal of Sports Physiology and Performance, 2022)
Purpose: The study aimed to identify the variables that differentiate judo athletes at national and regional levels. Multivariable analysis was applied to biomechanical, anthropometric, and Special Judo Fitness Test (SJFT) data.